Pelatihan Strategi Penyusunan Soal Pemecahan Masalah untuk Meningkatkan Keterampilan Berpikir Matematis pada Guru SD Kab. Kampar - Rusdial Marta; Fadhilaturrahmi; Aria Heldayani; Subariah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to develop students' mathematical thinking skills through problem-solving problem-solving strategy training for elementary school teachers in Kampar Regency. The training consisted of several sessions that combined theory, practice, and evaluation of questions prepared by participants. The results showed that the training successfully improved teachers' ability to prepare questions that not only tested basic understanding but also encouraged students to think critically and creatively. Teachers reported increased confidence in preparing more challenging and applicable questions, which could stimulate students' mathematical thinking skills. Although there were some challenges in determining the level of difficulty of the questions, the evaluation results showed that the training had a positive impact on improving the quality of mathematics learning. Post-training mentoring is needed to ensure the sustainability of the implementation of the questions that have been prepared. These findings indicate that practice-based training can improve the quality of mathematics education and provide significant benefits for the development of students' mathematical thinking skills.